Impact of Digital Bureaucracy on Business Compliance: A Field Study on Small Businesses Owners (SMEs) in Jeddah Governorate - Zantoot, Raed; Al-Shammari, Wael (The Arab Journal of Administration, 2025)
This study investigates the impact of digital bureaucracy on regulatory compliance among small businesses in Jeddah, Saudi Arabia, within the context of the Kingdom’s accelerated digital transformation initiatives. Utilizing a descriptive analytical approach, data were collected through an electronic questionnaire distributed to owners of small enterprises, resulting in 619 valid responses from over 7,000 distributed surveys. The study employed SPSS (V27) for data analysis, using multiple linear regression to examine the relationships between digital integration, digital platforms, user experience, and digital bias with compliance levels. The findings reveal that digital integration had the strongest positive influence on compliance (b = 0.423, p = 0.001), followed by user experience (b = 0.377, p = 0.002). Digital bias showed a significant negative effect (b = -0.312, p = 0.004), while the multiplicity of platforms had a weaker yet statistically significant negative impact (b = -0.211, p = 0.013). These results highlight the dual role of digital bureaucracy, where enhanced integration and user-centric design promote compliance, but fragmented platforms and digital biases can hinder regulatory adherence. The study recommends enhancing the interoperability of government digital platforms, improving user experience design, and systematically addressing digital biases to foster a more inclusive and efficient regulatory environment. These findings support the objectives of Saudi Arabia’s Vision 2030 in promoting a thriving economy and an integrated digital government.